Answer:
Part 1: Find (f/g)(4) = 3
Part 2: Find (f+g)(4) = 28
Explanation:
Part 1: Find (f/g)(4):
(f/g)(4) means divide f function by g function and simplify it. Then plug in 4 into x of that simplified function.
Let's do this:
![(x^2+2x-3)/(x^2-9)\\=((x+3)(x-1))/((x-3)(x+3))\\=(x-1)/(x-3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/6psbgsfwyhqbqriydpwzjwbvqd9kt3v4fv.png)
Plugging in 4 into x gives us:
![(x-1)/(x-3)\\=(4-1)/(4-3)\\=(3)/(1)\\=3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/vfrgzuw4xchjx5mjg1i93pn1uh6s3384wx.png)
The answer is 3
Part 2: Find (f+g)(4):
(f+g)(4) means add f function and g function and simplify it. Then plug in 4 into x of that simplified function.
Let's do this:
![(x^2+2x-3)+(x^2-9)\\=2x^2+2x-12](https://img.qammunity.org/2020/formulas/mathematics/middle-school/kkf903fa0ajuzyl8cjrdu073gyfdoziy2z.png)
Plugging in 4 into x gives us:
![2x^2+2x-12\\=2(4)^2+2(4)-12\\=28](https://img.qammunity.org/2020/formulas/mathematics/middle-school/arelbtl660t6filwzsqe24i3axi2679tqj.png)
The answer is 28